Pemanfaatan artificial intelligence dalam manajemen risiko perbankan syariah - bilal, imam jagat (Maliki Interdisciplinary Journal, 2025)
This study aims to analyze the application of Artificial Intelligence (AI) technology in risk management in Islamic banking. The focus includes how AI is used to detect, monitor, and mitigate risks such as credit, operational, and liquidity risks. In addition, this study assesses the effectiveness of AI in improving the efficiency and accuracy of decision-making in accordance with sharia principles. This research method uses a descriptive qualitative approach through a literature study of recent scientific journals. The results show that AI is able to strengthen the early risk detection system, automate the financing process, and improve the operational efficiency of Islamic banks. However, there are challenges in the form of human resource readiness, limited technological infrastructure, and the need for sharia-compliant regulations. This study recommends strengthening the Islamic digital ecosystem that is balanced between technology and Islamic values.